Illat, Hilah, dan Hikmah Sebagai Pertimbangan Perubahan Hukum Islam - Abdur Rakib; Zakiyah Muhammad Jamil (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
This research is substantively looking for the position of the meaning and benefits of a legal statement in Islamic fiqh. So as to find the root of the problem and the reasons for the stipulation of a law against mukallafin. This of course has to approach and consider asbab and eat the occurrence of an activity that is labeled the law by Shari '. So that the details of the rule of law in the context of the place can be explained and adjusted to the demands of the time. The use of theory in this study is to consider the opinions of the scholars (library research) by looking for details on the reasons for the enforcement of a legal instrument in a social community as well as the timing and circumstances of the law. The results of this study indicate that understanding the illat of law is a necessity in a consideration of Islamic law. Meanwhile, understanding the law and the wisdom of law, especially in terms of the role of changing a law according to time and place, is also something that cannot be avoided.